Safety Assessment of Buried Pipeline during Pile Driving Vibration in Offshore Engineering. Issue 7 (2nd October 2016) - Su, Jingbo; Cai, Guojun; Li, Jianfeng; Zhu, Ruihu; Qin, Wanggen; Zhai, Qiu
Abstract : To assess the impact of pile driving on adjacent submarine pipelines during the reconstruction of a pier berth, the local damage model of submarine pipelines is established to explore the safety thresholds of the particle peak velocity and horizontal displacement. The results are analyzed and adjusted by the existing standards and the corresponding literatures. Then, a three-dimensional numerical model is presented to assess the feasibility of the construction of piles by the obtained safety limits, in which the nonlinear behavior of the soil and stress–seepage coupling analysis are considered. After the construction, the safety of submarine pipelines is rechecked by the measured value of the particle peak velocity and horizontal displacement. Meanwhile, the propagation law of vibration, the horizontal displacement of underground soil, and the pore pressure during pile driving are explored. The results indicate that the construction of piles of 2# mooring pier did not cause damage to adjacent submarine pipelines. However, the construction of piles of 1# mooring pier which is nearer may cause damage to submarine pipelines.